Status and Dynamics of Forests in Germany Results of the National Forest Monitoring - Wellbrock, Nicole; Bolte, Andreas (Ecological Studies, 2019)
Life sciences; Ecology ; Forestry; Soil science; Soil conservation; Sustainable development; Geobiology